The anatomy of empathy: Vicarious experience and disorders of social cognition - Lockwood, P (Elsevier, 2016)
Empathy, the ability to vicariously experience and to understand the affect of other people, is fundamental for successful social-cognitive ability and behaviour. Empathy is thought to be a critical facilitator of prosocial behaviour and is disrupted in a number of psychiatric and neurological disorders. Research has begun to uncover the neural basis of such 'vicarious experience', which has been studied as a proxy measure of empathy. Together, these studies have identified portions of the insula and anterior cingulate cortex as critically involved. A key debate is whether overlapping or non-overlapping brain areas respond to personal and vicarious experience. This review will highlight emerging evidence for both types of brain response. Importantly, animal models have suggested that there are central divisions between the anterior cingulate gyrus and anterior cingulate sulcus that may be crucial for understanding social behaviour. Attention to this specific anatomy of vicarious processing could therefore help shed light on the functional profile of empathy. Studies in individuals with psychopathy and autism spectrum disorders have found that vicarious experience is atypical. However, the precise nature of these atypicalities is mixed. Understanding the mechanisms of vicarious experience can enhance our knowledge of the neural basis of empathy and, ultimately, help those with disorders of social cognition and behaviour.